Magnateria PRL [Seria znaczków podziemnych] . The aristocracy of People's Republic of Poland. Series of unofficial stamps - Poczta Solidarność. (Poczta Solidarność)
Black and red print on white paper with perforation. Series with "Poczta Solidarność" imprint represents caricatures of three Communist leaders: Wojciech Jaruzelski, Czesław Kiszczak and Edward Gierek. Each image is accompanied with a nickname and a coat of arms. Price: 50 zł per stamp.